Convergence of consumption patterns during macroeconomic transition: A model of demand in Ireland and the OECD - Sean Lyons; Karen Mayor; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2007)
This study uses country-level panel data on consumption in Ireland and seven other OECD countries to examine the evolution of Irish consumption patterns as Ireland underwent rapid macroeconomic growth. Consumption levels obviously increased due to substantially higher incomes, but it is less clear how the shares of different types of goods purchased have changed or whether Ireland's consumption mix has converged with that of other high-income countries. Rankings based on a simple distance measure of consumption similarity suggest that Ireland moved from a low-income pattern similar to Portugal or Greece to a high-income pattern like that of Canada between 1995 and 2003. Using static and dynamic Almost Ideal Demand System models, we first estimate long- and short-run Irish price and income elasticities for nine categories of commodities between 1976 and 2003. These results provide evidence of substantial habit formation in aggregate consumption. We then estimate a long-run cross-country model covering six aggregate commodity groups between 1975 and 2003. The analysis shows that Ireland's demand parameters remain more similar to those of Greece than to higher-income OECD countries in the sample. Although Ireland has overtaken most other OECD countries in per capita income, it is still converging to a higher-income consumption pattern. We foresee further convergence of Irish expenditure patterns towards a pattern typical of high-income countries.
Keywords: D12; E2; F15; 330; Macroeconomic transition; Almost Ideal Demand System; Consumption Patterns; Ireland; OECD; Systemtransformation; Konsumentenverhalten; Nachfragesystem; Panel; Schätzung; Irland; OECD-Staaten